EuroHYP-1: European Multicenter, Randomized, Phase III Clinical Trial of Therapeutic Hypothermia plus Best Medical Treatment vs. Best Medical Treatment Alone for Acute Ischemic Stroke. Issue 5 (July 2014) - van der Worp, H. Bart; Macleod, Malcolm R.; Bath, Philip M. W.; Demotes, Jacques; Durand-Zaleski, Isabelle; Gebhardt, Bernd; Gluud, Christian; Kollmar, Rainer; Krieger, Derk W.; Lees, Kennedy R.; Molina, Carlos; Montaner, Joan; et al.
Rationale: Cooling reduced infarct size and improved neurological outcomes in animal studies modeling ischemic stroke, and also improved outcome in randomized clinical trials in patients with hypoxic-ischemic brain injury after cardiac arrest. Cooling awake patients with ischemic stroke has been shown feasible in phase II clinical trials. Primary aim: To determine whether systemic cooling to a target body temperature between 34·0 and 35·0°C, started within six-hours of symptom onset and maintained for 24 h, improves functional outcome at three-months in patients with acute ischemic stroke. Design: International, multicenter, phase III, randomized, open-label clinical trial with blinded outcome assessment in 1500 patients aged 18 years or older with acute ischemic stroke and a National Institutes of Health Stroke Scale score of 6 up to and including 18. In patients randomized to hypothermia, cooling to a target body temperature of 34–35°C will be started within six-hours after symptom onset with rapid intravenous infusion of refrigerated normal saline or a surface cooling technique and maintained for 24 h with a surface or endovascular technique. Patients randomized to hypothermia will receive pethidine and buspirone to prevent shivering and discomfort. Primary outcome: Score on the modified Rankin Scale at 91 days, as analyzed with ordinal logistic regression and expressed as a common odds ratio. Discussion With 750 patients per intervention group, this trial has 90% power to detect 7% absolute improvement at the 5% significance level. The full trial protocol is available athttp://www.eurohyp1.eu . ClinicalTrials.gov Identifier: NCT01833312.